EFFECT OF MIXTURE OF ZEOLITE AND FERTILIZER APPLICATION ON PRODUCTION OF SWEET POTATO - R. Sugianto (Jurnal Zeolit Indonesia, 2005)
Sweet potatoes are more sensitive to fertilization of Nitrogen (N) and Potassium (K), among other macro nutrient elements. Theoretically, in order to produce one ton of this comodity, at least 3 kg N, 9 kg K, and 2 kg P are needed. But in fact actually, urea as a Nitrogen source that might be added to soil commonly evaporated in other way the KCl as the Potassium fertilizer easily leached down from soil profile and thus the plant productivity much lower. Objectives of this research are to study the influence of zeolites addition to increasement of nutrient absorption in soil by Sweet Potatoes. The research was conducted from February - June 2003 in District of Katibung, Jati Agung, Merbau Mataram, then from March-July 2003 in District of Panjang, and April-August 2003 in District of Waway Karya by using Complete Randomized Block Design with 3 replication. Each plot consists of 7 planting area (sized 35 m2) and planting distance is 100 cm x 25 cm, or plant density 140/plot. Zeolites is applied in application level of 30 % from total weight of fertilizer 350 kg/Ha. Bedeng size measure 30 cm and wide 60 cm. Zeolite used with dose 30 % from or equals to 105 kg zeolites/ Ha, Result of crop yield that showed by tuber weight both the small sized or the large sized tuber are optimalized in treatment C which 105 kg/ha zeolite. It could be explained because addition of zeolites in fertilizer increase the nutrient absorption by the crop planted. In all research locations, treatment C yielded the most beneficiary production of Sweet potatoes. Tuber root weight in Chinesse Fertilizing treatment lower than other fertilizer because the nutrients are much slower released in the soil profile.